The scaling of game-changer business models to address societal grand challenges - Gunaratne, Denanjalee; Sinkovics, Noemi; Sinkovics, Rudolf R.; Molina-Castillo, Francisco-Jose (Emerald, 2025)
Purpose This viewpoint paper aims to identify and illustrate the underlying logics of game-changer business models and situate them within the broader academic discourse on sustainable business model innovation and international business. This paper also examines the factors that influence the potential and actual scaling of these models. Design/methodology/approach This paper examines 17 cases identified as game-changers from the existing literature, the World Investment Forum’s Game Changers Summit and by scanning the outcomes of high-profile business competitions. These organizations aim to develop innovative solutions to address issues such as food security, climate change, plastic pollution, waste management, water security, sanitation, economic growth and the energy crisis. Findings The authors identify six recurring patterns or “logics” that characterize these game-changers: place-based solutions scalable through global relevance; leveraging the opportunities provided by advanced technologies; a “land-to-lab” approach for innovation; multi-stakeholder collaboration; the ability to tap into multiple funding sources; and a blend of vision, science and management capabilities. Originality/value The authors highlight how the meaning attached to particular terms, such as game-changers, can evolve over time. The findings and the subsequent theorizing outline how the concept of game-changers overlaps and differs from other concepts such as sustainable business models, blue ocean and disruptive innovators. By deriving observable logics from these cases, the authors provide a frame of reference to facilitate the comparison of findings across time and space regardless of how these business models are labeled.
Keywords: Game-changer business models; Sustainable business model innovation; Grand societal challenges; Impact-driven scaling; Born-global firms; Inclusive innovation; InnoLab; InnoLab